Immunhistochemical exepression of ER/PR in cytological and histopathological preparation of infiltrative ductal carcinoma of breast: comparation clinicopathological study - abduljabbar, Mona A.; ali, Sahira A.; AL.alwan, Nada A . (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Breast cancer is the leading cause of cancer death among women worldwide and in Iraq.Objectives: To evaluate the reliability of the immunocytochemical method in breast carcinoma aspirates with those obtained by immunohistochemistry of the corresponding excised breast tissue sections.Patients and methods: This is a prospective study. A total of (41) patient complain from malignant breast lump and (10) cases with benign mass (fibro adenoma) visited the Oncology Teaching Hospital in the Medical City in Baghdad during the period from the first of April 2012 to the end of December 2012. FNA sample taken for routine cytopathological and immuncytological study and the patient where followed up and immunhistological study was done for mastectomy or tissue biopsy samples.Results: The diagnostic sensitivity, specificity, PPV, and NPV of estrogen receptor ICC staining as Compared to the ER IHC were 92%,62%,50% and 95% respectively. The overall accuracy was 59.2%.The diagnostic sensitivity, specificity, PPV, and NPV of progesterone receptor ICC staining as Compared to the PR IHC were 93%, 62%, 58%, and 94% respectively. The overall accuracy was 73.2%Conclusion: There was no statistically significant correlation between ER , PR expression in both ICC and IHC